Pergeseran Nilai dan Praktik Hukum Waris Adat di Masyarakat Multikultural Indonesia - janeko, janeko (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
Shifting values in the practice of customary inheritance law in Indonesia is an inevitable phenomenon along with social, economic, and cultural developments in a multicultural society. Traditional inheritance law, which was initially based on the principles of kinship, deliberation, and social balance, now faces challenges due to the inclusion of modern values, national laws, and religious influences. This study aims to analyze the dynamics of these value shifts, the factors that drive change, and their implications for the social order of Indigenous Peoples. The research method used is juridical-sociological approach with literature study. The results showed that the shift in the value of customary inheritance law is more influenced by modernization, urbanization, and awareness of gender equality. This shift has a positive impact in the form of the growth of the value of justice and the protection of women's rights, but also causes negative impacts such as the weakening of social cohesion and the fading of cultural identity. Thus, a reconstruction strategy of customary inheritance law that is adaptive to the Times is needed, without eliminating the values of local wisdom that form the main foundation of customary law.